Psychiatric manifestations of HIV disease - Rameshboobathi K.; Rajeshkannan N (International Journal of Medical Research and Review, 2019)
Background: The appearance of AIDS on the medical and social scene in the early 1980 has been followed by worldwide spread of the disease and escalating numbers of persons affected. the first case was detected in 1984. For the first time in a worldwide epidemic, it has been necessary to try to change fundamental aspects of the human behavior by education and the dissemination of knowledge about psychiatric manifestations.Aim: To find out the psychiatric manifestations of HIV disease.Methods & Materials: 37 patients and 20 controls were taken up for evaluation of psychopathology. It’s a prospective study. Sociodemographic proforma, Socioeconomic Scale, Trail making A & B tests, color cancellation test, Raven's progressive matrices, Wechsler scale for memory, Linguistic fluency test were used.Results: Persons with HIV were having psychiatric manifestations like, Adjustment disorders, Depression, suicide, schizophrenia, Mild cognitive impairment to Dementia were noted among HIV and associated illnesses.Conclusion: Proper treatment adherence, counselling, follow up will improve the patient’s wellbeing.